Integrasi Komunikasi Formal-Informal sebagai Akselerator Budaya Hospitality di Industri Perhotelan - Fazar Ramadhan; Dwi Prasetyo (Yayasan Lentera Avanya Nagari, 2026)
The hospitality industry operates under rapid, 24-hour service demands, making interdepartmental communication critical to guest experience. This qualitative intrinsic case study examines how formal and informal communication are integrated to strengthen hospitality culture at Hotel Shangri-La Surabaya. Data were collected through semi-structured interviews with six informants from Food and Beverage, Front Office, Housekeeping, Banquet, and Guest Relations and analyzed thematically. Four interrelated themes emerged: formal direction, informal adaptation, feedback and correction, and cultural reinforcement. Formal channels such as briefings, BITE meetings, SOPs, and email align service standards and priorities, while WhatsApp groups, handy talkies, and face-to-face coordination enable rapid operational adaptation. Feedback, leader-mediated interpretation, and message redundancy reduce communication distortion, whereas respect, ownership, teamwork, and appreciation reinforce hospitality behavior. Barriers include unread digital messages, misinterpreted chat tone, shift gaps, and sudden operational changes. The study proposes a four-stage communication model linking organizational direction, real-time adaptation, corrective feedback, and cultural reinforcement to empathy, responsiveness, personalization, and service recovery. Industri perhotelan beroperasi dalam tuntutan layanan 24 jam yang cepat, sehingga komunikasi antardepartemen menjadi faktor kritis bagi pengalaman tamu. Studi kasus intrinsik kualitatif ini mengkaji bagaimana komunikasi formal dan informal diintegrasikan untuk memperkuat budaya hospitality di Hotel Shangri-La Surabaya. Data dikumpulkan melalui wawancara semi-terstruktur dengan enam informan dari Food and Beverage, Front Office, Housekeeping, Banquet, dan Guest Relations, kemudian dianalisis secara tematik. Analisis menghasilkan empat tema yang saling berkaitan: formal direction, informal adaptation, feedback and correction, dan cultural reinforcement. Kanal formal seperti briefing, BITE meeting, SOP, dan email menyelaraskan standar serta prioritas layanan, sedangkan grup WhatsApp, handy talky, dan koordinasi tatap muka memungkinkan adaptasi operasional secara cepat. Umpan balik, penerjemahan informasi oleh pemimpin, dan redundansi pesan mengurangi distorsi komunikasi, sementara respek, ownership, teamwork, dan apresiasi memperkuat perilaku hospitality. Hambatan meliputi pesan digital yang tidak terbaca, salah tafsir nada chat, kesenjangan shift, dan perubahan operasional mendadak. Penelitian ini menawarkan model komunikasi empat tahap yang menghubungkan arahan organisasi, adaptasi real-time, koreksi umpan balik, dan penguatan budaya dengan empati, responsivitas, personalisasi, dan service recovery.